Kultura narodowa detonatorem nienawiści? Przemyślenia inspirowane lekturą esejów Ivana Čolovicia .......... 217 - Bujwid-Kurek, Ewa (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
NATIONAL CULTURE AS A DETONATOR OF HATE? THOUGHTS INSPIRED BY READING THE ESSAYS OF IVAN ČOLOVIĆThe research aim of the article entitled: “National culture as a detonator of hate? Thoughts inspired by reading the essays of Ivan Čolović” was an attempt to answer the question of whether national culture can be a detonator – a kind of explosive material that provokes hate both within the political system and between individual nations. Based on the essays of one of the outstanding Serbian intellectuals, Ivan conclude that, unfortunately, national culture is undoubtedly a kind of detonator of hate, which can be confirmed not only by the war in the 1990s with the participation of post-Yugoslav countries, but also by the political situation still present in these countries.